Development of a spatial skills test for 4th grade primary school students: validity and reliability study - Elif Aydın-Çolak; Neslihan Şahin; Mustafa Kasım Kıroğlu (Frontiers in Psychology, 2026)
Although several instruments have been developed to assess spatial skills, most were designed for older students, emphasize specific components of spatial ability, or have not been specifically designed to reflect the developmental characteristics and mathematics curriculum of fourth-grade primary school students. Therefore, this study aimed to develop a valid and reliable spatial skills test specifically designed for fourth-grade primary school students. The study employed a quantitative methodological instrument development design. First, a literature review was conducted to generate an item pool, after which the test’s content validity was established through expert evaluations. The draft test was administered to 360 fourth-grade students attending public primary schools in the Black Sea Region of Türkiye during the 2024–2025 academic year. Item difficulty and discrimination indices, corrected item–total correlations, lower–upper group comparisons, the Kuder–Richardson-20 (KR-20) reliability coefficient, confirmatory factor analysis (CFA), and Rasch model analysis were used to evaluate the instrument’s psychometric properties. The findings resulted in a final 23-item test consisting of three dimensions: spatial visualization, spatial relations, and spatial orientation. The KR-20 coefficient was 0.827, indicating good internal consistency, while the Rasch analysis demonstrated acceptable item fit and satisfactory person separation reliability. Although the CFA provided partial support for the proposed three-dimensional structure, the construct validity evidence was strengthened by the complementary findings obtained from the Rasch model and classical test theory analyses. Overall, the findings indicate that the developed instrument provides promising evidence of validity and reliability for assessing the spatial skills of fourth-grade primary school students.